Proceedings of the 2nd International Workshop on Procedural Content Generation in Games 2011
DOI: 10.1145/2000919.2000928
|View full text |Cite
|
Sign up to set email alerts
|

Semantic constraints for procedural generation of virtual worlds

Abstract: Procedural generation of virtual worlds is a promising alternative to classical manual modelling approaches, which usually require a large amount of effort and expertise. However, it suffers from a number of issues; most importantly, the lack of user control over the generation process and its outcome. Because of this, the result of a procedural method is highly unpredictable, rendering it almost unusable for virtual world designers.This paper focuses on providing user control to deliver an outcome consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although designed for creating game levels, this approach still requires a large amount of user input with desired game design elements having to be manually expressed by the user in the sketch. Another technique proposed by Smelik et al [40] used two types of constraints to control the generation process of virtual worlds: semantic constraints and feature constraints. Feature constraint is linked to a single feature in the terrain (e.g.…”
Section: B Gameplay Requirement-based Terrain Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although designed for creating game levels, this approach still requires a large amount of user input with desired game design elements having to be manually expressed by the user in the sketch. Another technique proposed by Smelik et al [40] used two types of constraints to control the generation process of virtual worlds: semantic constraints and feature constraints. Feature constraint is linked to a single feature in the terrain (e.g.…”
Section: B Gameplay Requirement-based Terrain Generationmentioning
confidence: 99%
“…Andereck's [38] work focused on generating terrain to conform to a desired path, which may be useful as a terrain generation component, but is still far from being a complete terrain level generator that incorporates gameplay elements. Smelik's approach includes game design in a terrain and uses semantic constraints that can interact with the terrain to ensure it meets the desired design of a user [40]. Their results showed that using semantic constraints is a viable approach towards incorporating gameplay elements in terrain generation, but their approach is not scalable.…”
Section: Analysis Of the State Of The Artmentioning
confidence: 99%
“…The challenge with constraint-based approaches comes largely in determining an appropriate representation for facts about the generated content, and with debugging a set of complex, interrelated constraints. This approach has been used extensively in tools for designers [4,46,52].…”
Section: Constraint Satisfactionmentioning
confidence: 99%
“…Direct manipulation involves the player actively altering the generated content to provide additional constraints to the generator. This form of manipulation is more commonly seen in PCG-enabled design tools [46,52], rather than games themselves. The Spore Creature Creator [26], a design tool offered as part of the game Spore [27], offers this kind of interaction.…”
Section: Building Blocks Game Stage Interaction Type Player Experiencementioning
confidence: 99%
“…It is composed of "feature sub-constraints" mapped to low-level operations (e.g. the height of trees) [37]. Indeed, constraints are not always geometric or even virtual: table 1 shows a list of possible issues, situations or requirements which can have a constraining influence on VR interactions.…”
Section: Constraintsmentioning
confidence: 99%